2007
DOI: 10.1016/j.jsg.2007.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Is plane strain a valid assumption in non-cylindrical fault-cored folds?

Abstract: Many algorithms assume plane strain to construct, model and restore fault-cored folds. Using mechanical models that allow heterogeneous transport in three dimensions, we explore the distribution and magnitude of out-of-plane transport in plunging fault-cored anticlines and provide guidelines of where plane strain should and should not be applied. We developed a new technique of incrementing infinitesimal elastic strains to produce folds with aspect ratios similar to natural folds. Map views of displacement vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Folds produced within relatively thin layering (layers several times thinner than the wavelength) can grow to 4–5 times the amplitude of a fold in a medium without layering. Amplification through flexural slip folding was also noted by Shackleton and Cooke ().…”
Section: Kinematics and Mechanics Of Fault‐cored Anticlinessupporting
confidence: 54%
See 1 more Smart Citation
“…Folds produced within relatively thin layering (layers several times thinner than the wavelength) can grow to 4–5 times the amplitude of a fold in a medium without layering. Amplification through flexural slip folding was also noted by Shackleton and Cooke ().…”
Section: Kinematics and Mechanics Of Fault‐cored Anticlinessupporting
confidence: 54%
“…However, as discussed in more detail below, mechanical analyses of fault‐related folding have largely focused on passive folding by slip on faults; the mechanical layers required for buckle folding are absent in many analyses. Notable exceptions are the numerical simulations of Shackleton and Cooke () and Albertz and Lingrey () and analogue experiments of Bonanno et al () that showed that folding of layers above a blind fault is enhanced by allowing flexural slip at layer contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Given that area is a function of the bed thickness and the bed length, and if bed thickness is assumed to remain constant during deformation, it is possible to use the preservation of line lengths as an assessment of whether a section is restorable (Dahlstrom, 1969). In reality, bed thickness changes in fold cores due to mudstone (shale) thickening and out-of-plane transport (Shackleton and Cooke, 2007). For bed thickness to remain constant, deformation must be accommodated by bedding parallel slip (Tanner, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…With ongoing contraction, on either side of the pinned portions of the folds, there is a component of out-of-plane motion (Fig. 14B), where displacement vectors on the faults deviate from the E-W contraction (Shackelton and Cooke, 2007). This type of system can explain key components of the overall kinematic development in the Ballarat East gold deposit, which we have deduced from the sense of slip associated with mineralized veins and on faults.…”
Section: Integrated Model For Au Mineralization At Ballarat Eastmentioning
confidence: 82%